Cigarette Smoke-induced Oxidative Stress: A Systematic Review - Thirumalai, Dr. Thirunavukkarasu (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
In the present review, oxidative stress through free-radical generation in cigarette smokers has been widely investigated. Cigarette smoke exposure is a risk factor for human being as well as animals. Cigarette smoke exposure is known to contribute to excess reactive oxygen species generation, the role of oxidative stress and inflammation in Human. They cause lipid peroxidation, oxidation of proteins and damage to mainly lung, and other tissues. The findings obtained in this review work provide some clues for the impact of cigarette smoking.